HUBUNGAN KEKUATAN OTOT LENGAN DAN KELENTUKAN PINGGANG TERHADAP HASIL SHOOTING HOCKEY INDOOR TIM PUTRI KOTA BANDAR LAMPUNG - Maya Sari; Surisman; Suwarli; Joan Siswoyo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was conducted to examine the association between arm muscle strength and waist flexibility with shooting performance in the women’s indoor hockey team of Bandar Lampung City. A descriptive correlational design was employed in this study. The sample consisted of 30 participants. Data collection instruments included a push and pull dynamometer, standing stroke test, and indoor hockey shooting test. The research hypotheses were: (1) there is a relationship between arm muscle strength and shooting performance, (2) there is a relationship between waist flexibility and shooting performance, and (3) arm muscle strength and waist flexibility jointly relate to shooting outcomes. The findings revealed that: (1) arm muscle strength had a significant correlation with shooting performance (r = 0.486 > r table = 0.374), (2) waist flexibility was also significantly correlated with shooting performance (r = 0.410 > r table = 0.374), and (3) simultaneously, arm muscle strength and waist flexibility showed a significant combined relationship with shooting performance (r = 0.538 > r table = 0.374), contributing 29.01%.